KEGAGALAN TERAPI PADA KUSTA TIPE LEPROMATOSA DAN FAKTOR YANG MEMENGARUHINYA: SEBUAH LAPORAN KA - Joanne Natasha; Sri Linuwih Menaldi; Melani Marissa; Rizka Farah Hilma (Media Dermato-Venereologica Indonesiana, 2022)
Children is a group that is nine times more likely to contract leprosy. The finding of new cases of leprosy in children is a strong indicator that indicates the disease transmission is still ongoing. World Health Organization (WHO) in 2019 reported 14,981 out of 202,185 (7.4%) new cases of children. Cases of resistance to multidrug therapy (MDT) can be primary or secondary. It is important to detect drug resistance earlier considering children’s quality of life would be affected by leprosy complication. A 14 years old girl from Lebak Regency, Rangkasbitung, Banten was diagnosed as lepromatous type (LL) leprosy and a second grade disability on the 5th finger of her left hand. Unimproved clinical and increasing the morphological index (IM) on the 9th month of treatment from 0.16% to 1%, leading the patient experience the drug resistance. The polymerase chain reaction (PCR) examination did not show any mutation in the RpoB gene. Inadequate and irregular MDT consumption have the potential to cause secondary resistance and the risk of becoming primary resistance later. It is not easy to determine drug resistance in endemic areas. Morphological index monitoring should be closely watched before treatment is complete thus the modified therapy can be given earlier.